2014
DOI: 10.1017/s0714980814000452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Providing Care on the Risk of Leaving Employment in Canada

Abstract: Population aging is likely to lead to an increase in the number of people in need of assistance. It is well known that a large part of this assistance originates, and will continue to originate, from the network of relatives and friends. However, the effects of the provision of care on individuals' employment trajectories when this care is combined with employment of varying intensity or with childcare responsibilities have rarely been examined. The present study used proportional hazards models with the Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
(41 reference statements)
0
14
0
1
Order By: Relevance
“…Each of the six Canadian studies is a cross-sectional analysis drawing on the care-giver modules in Waves 16 and 21 of the General Social Survey (GSS). Since Latif (2006) and Proulx and Le Bordais (2014) do not control for care-giving intensity, we shall focus on results for the remaining four studies. Each of these found a negative and significant association between care-giving and the probability of being employed (Fast et al 2013; Jacobs et al 2014 a ; Lilly, Laporte and Coyte 2010; Williams, Wang and Kitchen 2013).…”
Section: Results By Country or Regionmentioning
confidence: 99%
“…Each of the six Canadian studies is a cross-sectional analysis drawing on the care-giver modules in Waves 16 and 21 of the General Social Survey (GSS). Since Latif (2006) and Proulx and Le Bordais (2014) do not control for care-giving intensity, we shall focus on results for the remaining four studies. Each of these found a negative and significant association between care-giving and the probability of being employed (Fast et al 2013; Jacobs et al 2014 a ; Lilly, Laporte and Coyte 2010; Williams, Wang and Kitchen 2013).…”
Section: Results By Country or Regionmentioning
confidence: 99%
“…Increasing care-giving responsibilities during mid-life may affect adult child carers’ participation in the labour market, as there is a time constraint on the ability to take up multiple roles (King and Pickard 2013; Loken, Lundberg and Riise 2014; Michaud, Heitmueller and Nazarov 2010; Plaisier, Broese van Groenou and Keuzenkamp 2015; Proulx and Le Bourdais 2014; Stewart 2013). Previous research in the United Kingdom (UK) has found that economically active individuals are less likely to provide care compared to inactive individuals (Vlachantoni 2010); and when informal carers are in paid work, they earn significantly less (Carmichael and Charles 2003; Evandrou, Glaser and Henz 2002; Proulx and Le Bourdais 2014). Van Houtven, Coe and Skira (2013), using US data, found that women care providers who continued working decreased their employment by three to ten hours per week.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using longitudinal data-sets allow the identification of changes in care-giving and employment status over time, informing the relationship between these roles within a lifecourse framework. Most of these recent studies emanate from the North American context (Lee and Tang 2015; Lumsdaine and Vermeer 2015; Proulx and Le Bourdais 2014; Skira 2015) with fewer studies from the UK (Carr et al 2016; King and Pickard 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012), accroissent la pression temporelle vécue par les travailleurs et inciteraient certains d'entre eux, en particulier les femmes en emploi à temps plein, à quitter leur emploi (Lero et collab. 2012 ;Proulx et Le Bourdais, 2014 ;Tremblay et collab. 2012). 20.…”
Section: Des Ménages De Plus En Plus Occupésunclassified